2024
DOI: 10.3390/ijms25063299
|View full text |Cite
|
Sign up to set email alerts
|

Post-Traumatic Expressions of Aromatase B, Glutamine Synthetase, and Cystathionine-Beta-Synthase in the Cerebellum of Juvenile Chum Salmon, Oncorhynchus keta

Evgeniya V. Pushchina,
Mariya E. Bykova,
Anatoly A. Varaksin

Abstract: In adult fish, neurogenesis occurs in many areas of the brain, including the cerebellum, with the ratio of newly formed cells relative to the total number of brain cells being several orders of magnitude greater than in mammals. Our study aimed to compare the expressions of aromatase B (AroB), glutamine synthetase (GS), and cystathionine-beta-synthase (CBS) in the cerebellum of intact juvenile chum salmon, Oncorhynchus keta. To identify the dynamics that determine the involvement of AroB, GS, and CBS in the ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 164 publications
(328 reference statements)
0
4
0
Order By: Relevance
“…The study of the properties of these cells is important from the point of view of the potential of their possible use in clinical practice in the treatment of neurodegenerative diseases, in particular, Alzheimer’s disease, Parkinson’s disease, traumatic brain injuries, and stroke. Effective post-traumatic repair in the cerebellum of juvenile chum salmon [ 13 , 14 ] and an increase in the number of GS+ and Aromatase-expressing, hydrogen sulfide-producing aNSPCs after long-term injury, as well as repeated injury, indicate effective neuroprotective mechanisms contributing to the successful recovery of the brain of salmon fish after trauma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study of the properties of these cells is important from the point of view of the potential of their possible use in clinical practice in the treatment of neurodegenerative diseases, in particular, Alzheimer’s disease, Parkinson’s disease, traumatic brain injuries, and stroke. Effective post-traumatic repair in the cerebellum of juvenile chum salmon [ 13 , 14 ] and an increase in the number of GS+ and Aromatase-expressing, hydrogen sulfide-producing aNSPCs after long-term injury, as well as repeated injury, indicate effective neuroprotective mechanisms contributing to the successful recovery of the brain of salmon fish after trauma.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of NSCs in the cerebellum and medulla oblongata of fish differs significantly from adult mammals, in which such foci of homeostatic neurogenesis are not preserved. Previous studies on juvenile chum salmon and masu salmon have shown that the cerebellum is dominated by neuroepithelial cells (NECs) located in various parts of the cerebellar body, dorsal matrix zone (DMZ), and granular eminence [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…The properties of NSPCs should be studied dynamically, over different time periods, when the initial potential of NSPCs and their ability to participate in the reparative process in acute and/or chronic injury can be estimated [21]. The combination of experimental modeling of chronic and repeated acute injury provides an answer to the question of if high neuronal performance is maintained during repeated injury, which may determine the special properties of embryonic and adult NSPCs and neuronal precursors of Pacific salmon [22]. In the periventricular areas of the mesencephalic tectum, mesencephalic tegmentum, telencephalon and brainstem, high proliferative activity of cells has been established during acute injury (3-7 days post-injury) [14,23,24].…”
Section: Biological Features Of Nscps In Pacific Salmonmentioning
confidence: 99%
“…Thus, increased neurogenesis in response to TBI can rapidly deplete the stem cell pool unless the intensity of neurogenesis is carefully regulated. In this sense, long-term monitoring can show how the proliferative properties of NSPCs of juvenile salmon change with chronic TBI, as well as with a combination of chronic and repeated TBI [22].…”
Section: Biological Features Of Nscps In Pacific Salmonmentioning
confidence: 99%